Development of genetic resistance to infection - Clark, David P. (FT Press Delivers elements, 2010)
"This Element is an excerpt from Germs, Genes, & Civilization: How Epidemics Shaped Who We Are Today (ISBN: 9780137019960) by David P. Clark. When a virulent epidemic rages, some humans survive and some die. Before vaccination, antibiotics, and modern medical technology, what decided who was fortunate and who was not? In addition to sheer luck, both social and biological factors affect the chances of catching a disease, as well as the likelihood of surviving"--Resource description page.